The Dayside Open/Closed Field line Boundary -Ground-based optical determination and examination - Johnsen, Magnar Gullikstad (Universitetet i Tromsø, 2011)
The papers of this thesis are not available in Munin: 1. M. G. Johnsen, D. A. Lorentzen, J, M. Holmes and U. P. Løvhaug: 'A model based method for obtaining the open/closed field line boundary from the cusp auroral 6300 Å[OI] red line' Journal of Geophysical research . Journal of Geophysical Research (2012), vol. 117, A03319, 13 pp. Available at http://dx.doi.org/10.1029/2011JA016980 2. M. G. Johnsen and D. A. Lorentzen: 'The dayside open/closed eld line boundary as seen from space- and ground-based instrumentation' Journal of Geophysical research (2012) vol. 117, A03320, 13pp. Available at http://dx.doi.org/10.1029/2011JA016983 3. M. G. Johnsen and D. A. Lorentzen: 'A statistical analysis of the optical dayside open/closed field line boundary' Journal of Geophysical research (2012), vol. 117, A02218, 12pp. Available at http://dx.doi.org/10.1029/2011JA016984 4. D. A. Lorentzen, J. Moen, K. Oksavik, F. Sigernes, Y. Saito and M. G. Johnsen: 'In situ measurement of a newly created polar cap patch', Journal of Geophysical research (2010), vol. 115, A12323. Available at http://dx.doi.org/10.1029/2010JA015710 The Open/Closed eld line Boundary (OCB) is the most important boundary in the magnetospheric system. On the dayside, the equatorward edge of the 6300 Å[OI] cusp aurora can be used as a proxy for the OCB. This work, which is a dissertation for the degree of philosophiæ Doctor consists of three scienti c papers focusing on the latitude of the optical cusp OCB and one paper focusing on polar cap patch generation mechanisms in the vicinity of the OCB. In Paper I we use modeling to demonstrate the variability of the cusp aurora with respect to vertical volume emission rate pro les and horizontal modulation owing to neutral wind. A meridian scanning photometer (MSP) simulator has been developed in order to study the manifestation of the cusp aurora in the MSP data from Svalbard. A method for obtaining the OCB location and nding the correct mapping altitude in order to transform the OCB location from MSP scan angle to ...